Speech-Enabled Interfaces for Travel Information Systems with Large Grammars - Zhao, Baoli; Allen, Tony; Bargiela, Andrzej (Applications and Innovations in Intelligent Systems XIV, 2006)
This paper introduces three grammar-segmentation methods capable of handling the large grammar issues associated with producing a real-time speech-enabled VXML bus travel application for London. Large grammars tend to produce relatively slow recognition interfaces and this work shows how this limitation can be successfully addressed. Comparative experimental results show that the novel last-word recognition based grammar segmentation method described here achieves an optimal balance between recognition rate, speed of processing and naturalness of interaction.